EFEKTIVITAS BANTUAN PROGRAM KELUARGA HARAPAN (PKH) DALAM MENGATASI PUTUS SEKOLAH SISWA MISKIN DI MTS SWASTA INSAN KESUMA LKMD KECAMATAN NAMO RAMBE - Alnuris Juaranas (Hijri, 2017)
This research aims to (1) to know the effectiveness of Family Hope Program (PKH) aid in overcoming the drop out of school (2) to know the role of principal, headmaster, parents and PKH assistant in helping to overcome the drop out of poor students (3) to know the supporting and inhibiting factors Which affect the Family Hope program (PKH) in overcoming the dropout. This research uses qualitative approach in the form of naturalistic. The research data was collected through observation, interview, and document analysis. Research data using data reduction techniques, data presentation and conclusions. School environment as well as in the classroom. Research subjects consist of principals, teachers, students, parents of students and PKH facilitators. The object of the research is the effectiveness of the Family Hope Program (PKH) aid in overcoming the drop out of school, which is listed in the general guidelines of PKH in 2016, the PKH companion decree, the madrasah profile and the data of drop out children.  Research instruments were interview guides, observation sheets, and field notes. Data analysis by qualitative descriptive method. The results of the research are: (1) Family Hope Program (PKH) aid has not been effective in overcoming drop out in MTs Swasta Insan Kesuma LKMD Kecamatan Namo Rambe. This is evident, on T.P. 2016-2017 there are 5 students who have dropped out at MTs Swasta Insan Kesuma LKMD Kecamatan Namo Rambe. However, the assistance of Family Hope Program (PKH) is able to reduce the dropout rate. This can be seen in T.P 2015-2016 students who have dropped out of 8 students and on T.P. 2016-2017 as many as 5 students. There was a decrease of 3 students who dropped out of school. If all poor students in MTs Swasta Insan Kesuma LKMD get the help of Family Hope Program (PKH), the possibility of dropping out at MTs Swasta Insan Kesuma LKMD Kecamatan Namo Rambe can be resolved. (2) The role of madrasah is as a motivator and policy maker for students and parents, the role of parents is as a motivator and facilitator for their children and the role of PKH assistant is as a motivator and verifier for parents and students. (3) factors supporting PKH assistance in overcoming the drop out are: government commitment, facilities provided to the participants of pkh, head of madrasah and the role of PKH assistant.